Evaluation of traps with food attractants for armyworm in chickpea - Fú Castillo, Agustín Alberto; Pérez Luna, Adriana Isabel; Corella Madueño, María Alba Guadalupe (Revista Mexicana de Ciencias Agrícolas, 2017)
The chickpea cultivation is a ffected by a lepidopteran complex, dominating Heliothis spp. and Spodoptera spp., which aff ect between 10-80% of their productivity. The combat of these pests is done by means of a visual sampling of eggs and subsequent application of insecticides; however, such sampling gives incorrect information of density and species present. Currently the use of baited traps with food attractants and sex pheromones complements the information generated by visual sampling and provides more accurate data for pest monitoring. The objective of the study was to evaluate food and sexual attractants and their ability to attract Spodoptera exigua moths in chickpea culture. The study used a completely randomized experimental design with three replicates. Treatments were commercial food attractant (Noctovi©), yeast + sugar, yeast, chelite pollen and S. exigua specific sex pheromone; and a witness without a sexual or attractant pheromone. The variables evaluated were populations of S. exigua moths, throughout the study period. The treatments that identified the greatest attraction and capture of adult moth in the trapped traps were treatments based on yeast plus sugar and the commercial Noctovi© , the latter being the one that obtained better results as attractant in the traps primed for the welded worm ( S. exigua ), which makes it a potential tool to be considered part of a comprehensive sampling program for this pest.